Farmers perception of constraints in plantain production in Ghana - Schill, P.F.; Afreh-Nuamah, K.; Gold, Cliford S.; Green, K.R. (Informa UK Limited, 2000)
Plantain (Musa AAB), a primary food crop in Ghana, is a key component in sustainable agricultural systems in high rainfall zones. Recently, there has been a substantial yield decline and reduction in plantation life. To elucidate the context in which intervention strategies should be developed, a Participatory Rural Appraisal (PRA) was conducted at five villages in the major plantain-producing belt of Ghana. The importance of plantain as a preferred food was confirmed, although farmers tended to sell plantain for cash income, using cheaper, less preferred alternatives for home consumption. Farmers identified decreasing soil fertility, the high cost of labour for weeding, pests and diseases, lack of good quality planting material and marketing-related issues as the major production constraints. Due to declining productivity in less fertile regions, plantain has been replaced with other food crops such as cassava and maize. Farmers overestimated the importance of insect pests but were unaware of the extensive damage that could be caused by nematodes and the foliar disease, black sigatoka. They observed, however, that pest damage is more severe when soil fertility is poor. Clearly, integrated pest management is likely to be most effective when practiced within the context of cropping systems management; sustainable strategies that are being developed for resource-limited plantain farmers in Ghana are discussed.